Evolution and Determinants of Weight Gain (by Height and Age) in Children Aged Two to 72 Months - Carlos Roberto Padovani (Academic Journal of Clinicians, 2023)
OBJECTIVES: a summary of the main aspects of the publications referring to a project conducted by the team in the last decade is recovered, with the aim of supporting the evaluation of sectoral public policy on dietary supplementation in childhood. METHODS: growth and development indicators were monitored quarterly for one year in peripheral populations aged two to 72 months, in Sorocaba, São Paulo. After carrying out a child census in two regions of the city, children attending daycare centers (164) were compared to the others (280). The nutritional impact was quantified through univariate analyzes (Kappa and Goodman inferential tests) and multivariate analyses. Biases and confounding were investigated and controlled. RESULTS: among many other information obtained, it was observed that the assisted group presented: 1) higher average age; 2) lower breastfeeding rate; 3) lower weight/height values at admission, with greater gains during evolution; 4) this improvement increased with the duration of exposure and was greater among older people. CONCLUSIONS: it is assessed that providing appropriate assistance to preschoolers today constitutes, in our environment, a relevant imperative of social order